2011
DOI: 10.1002/hbm.21466
|View full text |Cite
|
Sign up to set email alerts
|

The cerebral representation of temporomandibular joint occlusion and its alternation by occlusal splints

Abstract: Occlusal splints are a common and effective therapy for temporomandibular joint disorder. Latest hypotheses on the impact of occlusal splints suggest an altered cerebral control on the occlusion movements after using a splint. However, the impact of using a splint during chewing on its cerebral representation is quite unknown. We used functional magnetic resonance imaging (fMRI) to investigate brain activities during occlusal function in centric occlusion on natural teeth or on occlusal splints in fifteen heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
4
24
0
1
Order By: Relevance
“…A significant lateralized response, as described by others for occlusion (17,37) and for swallowing (57) was absent in our study for both tasks.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A significant lateralized response, as described by others for occlusion (17,37) and for swallowing (57) was absent in our study for both tasks.…”
Section: Discussionsupporting
confidence: 67%
“…Comparable to swallowing, a left hemispheric lateralization of bilateral occlusion of opercular areas to the dominant left hemisphere was reported (17,37). Overall, representational sites described during occlusion seem to be widely congruent to those described during swallowing (30).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Our results of normalization in the inferior temporal lobe and medial prefrontal cortex are consistent with a previous fMRI study of healthy subjects that found increased brain activity in the right and left temporal regions and prefrontal lobe related to occlusion with and without a splint (Lotze et al , ). In addition to the functional normalization in motor regions, the present results demonstrated normalized activation of the temporo‐frontal network and functional recovery of the DMN evoked by plasticity‐related changes, which may contribute to the mechanisms underlying the therapeutic effects of stabilization splints in TMDs patients.…”
Section: Discussionsupporting
confidence: 92%
“…The cerebellum plays a key role in motor coordination and learning and it is also active in mandible movements (Onozuka et al , ; Wong et al , ; Lotze et al , ). Previous studies found activation in cerebellum during jaw movements in healthy controls (Onozuka et al , ; Wong et al , ; Grabski et al , ).…”
Section: Discussionmentioning
confidence: 99%